PENERAPAN MODEL LEARNING CYCLE 5E (LC 5E) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X8 SMA NEGERI 2 SIAK HULU - Selvi Apriana; Sakur '; Jalinus ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research was classroom action research that aims to improve learning process and mathematics learning achievement with applied the cooperative learning think pair square structural approach. The subject of the research is students of class X8 SMAN 2 Siak Hulu in the second semester academic years 2013/2014. There are 36 students in the class, consist of 18 girls and 18 boys with heterogeneous academic ability. This research is execieted in two cycles, and at the of every cycle end carried out mathematics achievement test. Data collected through observation and mathematics achievement test. Analysis data of observation was performed with narrative descriptive analysis. This research result in showed an increase in students from the base score with the percentage 30,5 % to 52% on the first test and 69,45% on the second test. This research result in indicates that the Learning Cycle 5E (LC 5E) can improve learning process and students' mathematics learning outcomes math class X8 SMAN 2 Siak Hulu.Key words: Mathematics Achievement, Learning Cycle 5E (LC 5E), Class action research